An evaluation of community-based cognitive stimulation therapy: a pilot study with an Irish population of people with dementia. (14th July 2016) - Kelly, M. E.; Finan, S.; Lawless, M.; Scully, N.; Fitzpatrick, J.; Quigley, M.; Tyrrell, F.; O'Regan, A.; Devane, A.
Abstract : Objectives: Research shows that cognitive stimulation therapy (CST) improves cognitive function, quality of life, and well-being of people with mild–moderate dementia. Despite consistent evidence and recommendations, CST is not routinely available in Ireland post-diagnosis. The aim of the current research was to develop and evaluate community-based CST for people with mild–moderate dementia, run by the Alzheimer Society of Ireland across four pilot sites in Ireland. Methods: Participants with mild–moderate dementia attended once weekly CST sessions for 14 weeks. Baseline and post-intervention assessments were completed by CST participants, carers, and CST facilitators. Primary outcomes of interest for CST participants included quality of life (Quality of Life in Alzheimer Disease Scale), cognitive function (Montreal Cognitive Assessment), and subjective cognitive function (Memory Awareness Rating Scale-Functioning Subscale). Secondary outcomes included well-being, cognitive ability, satisfaction with cognitive performance, and engagement and confidence of CST participants; well-being of carers; and job satisfaction of facilitators. Post-intervention interviews supplemented quantitative analyses. Results: In total, 20 CST participants, 17 carers, and six CST facilitators completed evaluation assessments. Results showed that CST improved participants' satisfaction with cognitive performance ( p =0.002), level of engagement ( p =0.046), level of confidence ( p =0.026). Improvements on subjective cognitive function just fell short of significance ( p =0.055). Qualitative analysis of interview data identified consistent themes of cognitive and overall benefits of CST; and provided support for quantitative data. Conclusions: Community-based CST positively impacted the lives of people with dementia and their families. This study supports prior recommendations that CST should be made routinely available to people with mild–moderate dementia, particularly in light of the lack of post-diagnostic interventions currently offered in Ireland.